Electrochemistry at the Synapse - Shin, Mimi (Annu Rev Anal Chem (Palo Alto Calif), 2019)
Electrochemical measurements of neurotransmitters provide insight into the dynamics of neurotransmission. In this review, we describe the development of electrochemical measurements of neurotransmitters and how they started with extrasynaptic measurements, but now are pushing to synaptic measurements. Traditionally, behavioral measurements with biosensors or fast-scan cyclic voltammetry have monitored extrasynaptic levels of neurotransmitters, such as dopamine, serotonin, adenosine, glutamate, and acetylcholine. Amperometry and electrochemical cytometry techniques have revealed mechanisms of exocytosis, suggesting partial release. Advances in nanoelectrodes now allow spatially resolved, electrochemical measurements in a synapse, which is only 20–100 nm wide. Synaptic measurements of dopamine and acetylcholine have been made. In this article, electrochemical measurements are also compared to optical imaging and mass spectrometry measurements, and while these other techniques provide enhanced spatial or chemical information, electrochemistry is best at monitoring real-time neurotransmission. Future challenges include combining electrochemistry with these other techniques, in order to facilitate multisite and multianalyte monitoring.